Method for manufacturing silicon nitride substrate and silicon nitride substrate

By using enstatite microcrystalline glass and rare earth compounds as sintering aids, the high cost and easy cracking problems of silicon nitride ceramic substrates were solved, and high-strength, low-cost silicon nitride substrates were prepared.

CN120664885BActive Publication Date: 2026-11-06四川富乐华半导体科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510735287.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2026-11-06
Estimated Expiration
2045-06-04

AI Technical Summary

Technical Problem

Existing silicon nitride ceramic substrate fabrication processes are costly, have low flexural strength, and are prone to deformation and cracking.

Method used

By using enstatite microcrystalline glass and rare earth compounds as sintering aids to replace traditional magnesium oxide, silicon nitride substrates are prepared through steps such as ball milling, tape casting, debinding and sintering, which improves sintering density and enhances mechanical properties.

Benefits of technology

It reduces manufacturing costs, improves the flexural strength of silicon nitride substrates, prevents deformation and cracking, and possesses excellent mechanical properties and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120664885B_ABST
    Figure CN120664885B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a silicon nitride substrate and the silicon nitride substrate and belongs to the field of integrated circuit manufacturing, and comprises the following steps: S1, ball milling; S2, forming; S3, degreasing; S4, sintering: the degreasing sheet is sintered to form a silicon nitride sintered substrate; the sintering aid contains enstatite glass-ceramics and a rare earth compound, and the content of the silicon nitride, the enstatite glass-ceramics and the rare earth compound is as follows: 88-93 wt% of the silicon nitride, 4-7 wt% of the enstatite glass-ceramics and 2-5 wt% of the rare earth compound; the enstatite glass-ceramics is made of the following components: 50-55 wt% of raw sodium sand, 1-5 wt% of high alumina soil, 35-40 wt% of body burning talc, 1-5 wt% of anorthite, 1-5 wt% of potassium feldspar and 1-5 wt% of sodium feldspar. The application improves the bending strength of the silicon nitride ceramic substrate, avoids cracking and deformation and reduces the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of integrated circuit manufacturing, and particularly to a method for preparing a silicon nitride substrate and the silicon nitride substrate itself. Background Technology

[0002] Currently, with the rapid development of new energy vehicles, photovoltaics, wind power, integrated circuits, aerospace, 5G communications, and other fields, the emergence of third-generation semiconductors represented by SiC and GaN is driving power electronic devices towards higher power, integration, higher frequency, higher voltage, and higher current. Ceramic substrates serve as chip supports, electrical insulation, and heat conduction channels. The substrate has the highest thermal resistance along the heat conduction path and must transfer heat to the packaging shell in a timely manner, thus requiring high thermal conductivity. Furthermore, ceramic substrates must withstand thermal stress caused by thermal cycling and temperature gradients, therefore requiring excellent mechanical properties.

[0003] Silicon nitride ceramic substrates are now used as important heat dissipation substrate materials, requiring high thermal conductivity and excellent mechanical properties. In existing silicon nitride ceramic substrate fabrication processes, magnesium oxide is used as a sintering aid during sintering. While this provides high thermal conductivity and relatively good mechanical properties, it has the following drawbacks:

[0004] (1) The manufacturing cost is relatively high;

[0005] (2) The substrate has low flexural strength and is prone to deformation and cracking.

[0006] The above background information is provided to facilitate understanding of the present invention and is not intended to be publicly known technology disclosed to the general public prior to the application of this invention. Summary of the Invention

[0007] To address the aforementioned shortcomings, this invention provides a method for preparing a silicon nitride substrate, which improves the flexural strength of the silicon nitride ceramic substrate, avoids cracking and deformation, and reduces costs.

[0008] The technical solution is: a method for preparing a silicon nitride substrate, comprising the following steps:

[0009] S1, ball milling: take silicon nitride and sintering aid, mix and ball mill to form ceramic slurry;

[0010] S2, Molding: After degassing, aging and sieving, the ceramic slurry is cast into a silicon nitride green ceramic tape.

[0011] S3, Degreasing: Silicon nitride green ceramic belt is used for degreasing to remove organic matter from the green body and obtain degreasing sheet;

[0012] S4, Sintering: Degreased sheets are sintered to form a silicon nitride sintered substrate;

[0013] In S1, the sintering aid contains enstatite microcrystalline glass and rare earth compounds. The contents of silicon nitride, enstatite microcrystalline glass, and rare earth compounds are as follows:

[0014] Silicon nitride 88-93 wt%

[0015] 4-7 wt% of enstatite microcrystalline glass

[0016] Rare earth compounds 2-5 wt%

[0017] The enstatite microcrystalline glass is made of the following components:

[0018] 50-55 wt% of raw sodium sand ore

[0019] 1-5 wt% high-alumina

[0020] 35-40 wt% calcined talc in the billet

[0021] 1-5 wt% of anorthite

[0022] Potassium feldspar 1-5 wt%

[0023] Albite 1–5 wt%.

[0024] Furthermore, the enstatite glass-ceramic is prepared by the following steps:

[0025] Q1. Dry the raw sodium sand, high alumina clay, calcined talc, calcium feldspar, potassium feldspar, sodium feldspar, and other mineral raw materials separately to remove moisture.

[0026] Q2. Weigh out the raw sodium sand, high alumina clay, calcined talc for billet, calcium feldspar, potassium feldspar and sodium feldspar according to the formula, mix them evenly and place them in an alumina crucible.

[0027] Q3, the alumina crucible is placed in an air sintering furnace for sintering at a heating rate of 1-10℃ / min, a melting temperature of 1500-1600℃, and a holding time of 2-4h. Then the molten liquid is poured into a water tank for water quenching to obtain glass frit, and the glass frit is dry-ground to obtain glass powder.

[0028] Q4, glass powder is ball-milled for 1-3 hours to form a slurry;

[0029] Q5. Place the slurry in a spray granulation tower for granulation to obtain spherical powder. The spherical powder is then dry-pressed into block samples.

[0030] Q6. Enstatite microcrystalline glass was obtained by powder sintering of a block sample, wherein the heating rate was 1-10℃ / min, the nucleation temperature of the enstatite microcrystals was 800-900℃, the holding time was 1-2h, the crystallization temperature was 1100-1200℃, and the holding time was 2-4h.

[0031] Furthermore, in Q5, the particle size of the spherical powder D50 is 0.5–1.0 micrometers.

[0032] Furthermore, in S2, the aging time is 3–665 h, and the thickness of the green ceramic belt is 0.1–0.8 mm; in S3, the degreasing atmosphere is nitrogen, the flow rate is 100–300 L / min, the degreasing temperature is 500–600 °C, the degreasing time is 5–10 h, and the heating rate is 1–5 °C / min; in S4, the sintering atmosphere is nitrogen, the pressure is 1–3 MPa, the sintering temperature is 1750–1850 °C, the holding time is 3–6 h, and the heating rate is 1–5 °C / min.

[0033] Furthermore, the silicon nitride powder is α-Si3N4 with a purity >99% and a particle size D. 50 The range is 0.4–1.0 μm.

[0034] Furthermore, the rare earth compound is one of Yb2O3, Y2O3, or a mixture thereof.

[0035] The present invention also provides a silicon nitride substrate.

[0036] A silicon nitride substrate, made of the following main components:

[0037] Silicon nitride 88-93 wt%

[0038] 4-7 wt% of enstatite microcrystalline glass

[0039] Rare earth compounds 2-5 wt%

[0040] The enstatite microcrystalline glass is made of the following components:

[0041] 50-55 wt% of raw sodium sand ore

[0042] 1-5 wt% high-alumina

[0043] 35-40 wt% calcined talc in the billet

[0044] 1-5 wt% of anorthite

[0045] Potassium feldspar 1-5 wt%

[0046] Albite 1–5 wt%.

[0047] Furthermore, the silicon nitride substrate exhibits a flexural strength > 800 MPa, a thermal conductivity > 80 W / mK, and a density > 3.2 g / cm³. 3 Warpage ≤ 0.3%.

[0048] Furthermore, the enstatite glass-ceramic is prepared by the following steps:

[0049] Q1. Dry the raw sodium sand, high alumina clay, calcined talc, calcium feldspar, potassium feldspar, sodium feldspar, and other mineral raw materials separately to remove moisture.

[0050] Q2. Weigh out the raw sodium sand, high alumina clay, calcined talc for billet, calcium feldspar, potassium feldspar and sodium feldspar according to the formula, mix them evenly and place them in an alumina crucible.

[0051] Q3, the alumina crucible is placed in an air sintering furnace for sintering at a heating rate of 1-10℃ / min, a melting temperature of 1500-1600℃, and a holding time of 2-4h. Then the molten liquid is poured into a water tank for water quenching to obtain glass frit, and the glass frit is dry-ground to obtain glass powder.

[0052] Q4, glass powder is ball-milled for 1-3 hours to form a slurry;

[0053] Q5. Place the slurry in a spray granulation tower for granulation to obtain spherical powder. The spherical powder is then dry-pressed into block samples.

[0054] Q6. Enstatite microcrystalline glass was obtained by powder sintering of a block sample, wherein the heating rate was 1-10℃ / min, the nucleation temperature of the enstatite microcrystals was 800-900℃, the holding time was 1-2h, the crystallization temperature was 1100-1200℃, and the holding time was 2-4h.

[0055] Furthermore, the silicon nitride substrate is prepared by the following steps:

[0056] S1, ball milling: take silicon nitride and sintering aid, mix and ball mill to form ceramic slurry;

[0057] S2, Molding: After degassing, aging and sieving, the ceramic slurry is cast into a silicon nitride green ceramic tape.

[0058] S3, Degreasing: Silicon nitride green ceramic belt is used for degreasing to remove organic matter from the green body and obtain degreasing sheet;

[0059] S4, Sintering: Degreased sheets are sintered to form a silicon nitride sintered substrate.

[0060] Furthermore, in S2, the aging time is 3–665 h, and the thickness of the green ceramic belt is 0.1–0.8 mm; in S3, the degreasing atmosphere is nitrogen, the flow rate is 100–300 L / min, the degreasing temperature is 500–600 °C, the degreasing time is 5–10 h, and the heating rate is 1–5 °C / min; in S4, the sintering atmosphere is nitrogen, the pressure is 1–3 MPa, the sintering temperature is 1750–1850 °C, the holding time is 3–6 h, and the heating rate is 1–5 °C / min.

[0061] Invention principle and effects:

[0062] This invention replaces magnesium oxide with enstatite microcrystals in combination with silicon nitride and rare earth compounds, which lowers the liquid phase formation temperature and increases the amount of liquid phase, promotes particle rearrangement, and improves sintering density. The enstatite microcrystals have an extremely low coefficient of thermal expansion, which makes the blanks highly thermally stable in the high-temperature sintering zone and can effectively prevent the blanks from deforming and cracking. Moreover, the manufacturing process of enstatite microcrystals is simplified, and the cost is low compared to imported magnesium oxide additives. Attached Figure Description

[0063] Figure 1 This is a microstructure diagram of the silicon nitride sintered substrate in Embodiment 2 of the present invention;

[0064] Figure 2 This is a physical image of the silicon nitride sintered substrate of Embodiment 2 of the present invention. Detailed Implementation

[0065] The technical solution of the present invention will be described in detail below with specific embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention and not for limiting the claims of the present invention.

[0066] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "longitudinal," "lateral," "horizontal," "inner," "outer," "front," "rear," "top," and "bottom," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product of this invention is in use. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0067] In the description of this invention, it should also be noted that, unless otherwise explicitly specified and limited, the terms "set up," "open," "installed," "connected," and "communicate" should be interpreted broadly. For example, they can refer to fixed connection, detachable connection, or integral connection; they can refer to direct connection or indirect connection through an intermediate medium; and they can refer to the connection within two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0068] Unless otherwise specified, all inventions are existing technologies.

[0069] Unless otherwise specified, all materials involved in this invention are purchased from the market.

[0070] Example 1

[0071] A method for preparing enstatite microcrystals includes the following steps:

[0072] Q1. Dry the raw sodium sand, high alumina clay, calcined talc for billets, calcium feldspar, potassium feldspar, sodium feldspar, and other mineral raw materials separately to remove moisture.

[0073] Q2, take the dried raw sodium sand, high alumina clay, calcined talc for billets, calcium feldspar, potassium feldspar, and sodium feldspar from Q1, wherein the raw sodium sand is 50wt%, high alumina clay is 5wt%, calcined talc for billets is 38wt%, calcium feldspar is 2wt%, potassium feldspar is 2wt%, and sodium feldspar is 3wt%, mix them evenly, and place them in an alumina crucible.

[0074] Q3. Sintering is carried out in an air sintering furnace with a heating rate of 5℃ / min, a melting temperature of 1550℃, and a holding time of 3h. The molten liquid is then poured into a water tank for water quenching to obtain glass frit, which is then dry-ground to obtain glass powder.

[0075] Q4. Weigh out the glass powder, trioleic acid glyceride, ethyl cellulose and water from Q3, wherein the glass powder is 43wt%, the trioleic acid glyceride is 2wt%, the ethyl cellulose is 5wt% and the deionized water is 50wt%. Place them in a planetary ball mill jar, add 2 / 3 volume of alumina ceramic balls, and ball mill for 2 hours to obtain a slurry.

[0076] Q5. The slurry is placed in a spray granulation tower to obtain spherical powder with a D50 particle size of 0.5 to 1.0 micrometers. Then, it is dry-pressed into block samples at a pressure of 60 MPa.

[0077] Q6. Enstatite microcrystalline glass was obtained by powder sintering of the bulk sample; the heating rate was 5℃ / min, the nucleation temperature of the enstatite microcrystals was 850℃, and the holding time was 2h; the crystallization temperature was 1200℃, and the holding time was 4h.

[0078] In this embodiment,

[0079] The enstatite microcrystals prepared in this embodiment are used in Examples 2-6 below.

[0080] Example 2

[0081] The preparation of a high-strength silicon nitride substrate includes the following steps:

[0082] S1, Ball milling: Weigh silicon nitride, enstatite microcrystals and yttrium oxide to obtain a mixed powder, add dispersant, binder and organic solvent, wherein the dispersant accounts for 3% of the weight percentage of the mixed powder, the binder accounts for 10% of the weight percentage of the mixed powder and the organic solvent accounts for 150% of the weight percentage of the mixed powder, and ball mill for 30 hours to obtain ceramic slurry.

[0083] S2, Casting: Degas the ceramic slurry, control the slurry viscosity to 10000~15000cps, then age for 5 hours, sieve, then connect the casting machine head to start casting, control the casting machine cutter head height to 0.2~1.0, and after drying, obtain a green ceramic tape with a thickness of 0.1~0.8mm.

[0084] S3, Degreasing: The green ceramic belt is placed in a degreasing furnace to remove organic matter from the green body. The degreasing atmosphere is nitrogen, the flow rate is 100-300 L / min, the degreasing temperature is 500-600℃, the degreasing time is 10h, and the heating rate is 1-5℃ / min. After the organic matter in the green body is completely removed, a degreasing sheet is obtained.

[0085] S4, Sintering: Finally, the degreased sheet is placed in a pressure sintering furnace for sintering. The sintering atmosphere is nitrogen, the pressure is 1-3 MPa, the sintering temperature is 1800℃, the holding time is 5h, and the heating rate is 1-5℃ / min; finally, a silicon nitride sintered substrate is obtained.

[0086] In this embodiment S1, the composition is 91 wt% silicon nitride, 6 wt% enstatite microcrystals, and 3 wt% yttrium oxide. In this embodiment, the silicon nitride powder is α-Si3N4 powder with a purity >99% and a particle size D50 of 0.4–1.0 μm.

[0087] The microstructure of the silicon nitride sintered substrate obtained in this embodiment is shown in the figure below. Figure 1 Actual product image as shown Figure 2 .

[0088] Comparative Example 1

[0089] The difference between this comparative example and Example 2 is that in S1, 6 wt% of enstatite microcrystals was replaced with 6 wt% of magnesium oxide.

[0090] Example 3

[0091] The difference between this comparative example and Example 2 is that in S1, silicon nitride is 91 wt%, enstatite microcrystals are 7 wt%, and yttrium oxide is 2 wt%.

[0092] Example 4

[0093] The difference between this comparative example and Example 2 is that in S1, silicon nitride is 91 wt%, enstatite microcrystals are 5 wt%, and yttrium oxide is 4 wt%.

[0094] Example 5

[0095] The difference between this comparative example and Example 2 is that in S1, silicon nitride is 91 wt%, enstatite microcrystals are 4.5 wt%, and yttrium oxide is 4.5 wt%.

[0096] Example 6

[0097] The difference between this comparative example and Example 2 is that in S1, silicon nitride is 91 wt%, enstatite microcrystals are 4 wt%, and yttrium oxide is 5 wt%.

[0098] The thickness of the substrates prepared in Comparative Example 1 and Examples 2-6 was 0.32 ± 0.032 mm.

[0099] The silicon nitride substrates prepared in Examples 2-6 and Comparative Example 1 were tested, and their structures are shown in Table 1 below.

[0100] Table 1

[0101] <![CDATA[Bulk density (g / cm 3 )]]> Flexural strength (MPa) Thermal conductivity (W / mK) Warpage (‰) Example 2 3.25 850 85 1 Comparative Example 1 3.24 800 83 3 Example 3 3.22 820 81 3 Example 4 3.19 795 83 5 Example 5 3.17 760 84 6 Example 6 3.16 745 84 6

[0102] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a silicon nitride substrate, characterized in that, Includes the following steps: S1, ball milling: take silicon nitride and sintering aid, mix and ball mill to form ceramic slurry; S2, molding: After degassing, aging and sieving, the ceramic slurry is cast into a silicon nitride green ceramic tape. S3, Degreasing: Silicon nitride green ceramic belt is used for degreasing to remove organic matter from the green body and obtain degreasing sheet; S4, Sintering: Degreased sheets are sintered to form a silicon nitride sintered substrate; In S1, the sintering aid contains enstatite microcrystalline glass and rare earth compounds. The contents of silicon nitride, enstatite microcrystalline glass, and rare earth compounds are as follows: Silicon nitride 88~93 wt% Enstatite microcrystalline glass 4~7 wt% Rare earth compounds 2~5 wt% The enstatite microcrystalline glass is made of the following components: 50-55 wt% raw sodium sand ore 1-5 wt% high-alumina 35-40 wt% calcined talc in the billet 1-5 wt% of calcium feldspar Potassium feldspar 1~5wt% albite 1~5wt%; The enstatite microcrystalline glass is prepared by the following steps: Q1. Dry the raw sodium sand, high alumina clay, calcined talc, calcium feldspar, potassium feldspar, and sodium feldspar mineral raw materials separately to remove moisture. Q2. Weigh out the raw sodium sand, high alumina clay, calcined talc for billet, calcium feldspar, potassium feldspar and sodium feldspar according to the formula, mix them evenly and place them in an alumina crucible. Q3, the alumina crucible is placed in an air sintering furnace for sintering at a heating rate of 1~10℃ / min, a melting temperature of 1500~1600℃, and a holding time of 2~4h. Then the molten liquid is poured into a water tank for water quenching to obtain glass frit, and the glass frit is dry-ground to obtain glass powder. Q4, glass powder is ball-milled for 1-3 hours to form a slurry; Q5. Place the slurry in a spray granulation tower for granulation to obtain spherical powder. The spherical powder is then dry-pressed into block samples. Q6. Obtain enstatite microcrystalline glass by powder sintering of block samples, wherein the heating rate is 1~10℃ / min, the nucleation temperature of enstatite microcrystals is 800~900℃, the holding time is 1~2h, the crystallization temperature is 1100~1200℃, and the holding time is 2~4h. In Q5, the spherical powder D50 particle size is 0.5~1.0 micrometers; In S2, the aging time is 3~665h, and the thickness of the green ceramic belt is 0.1~0.8mm; in S3, the degreasing atmosphere is nitrogen, the flow rate is 100~300L / min, the degreasing temperature is 500~600℃, the degreasing time is 5~10h, and the heating rate is 1~5℃ / min; in S4, the sintering atmosphere is nitrogen, the pressure is 1~3MPa, the sintering temperature is 1750~1850℃, the holding time is 3~6h, and the heating rate is 1~5℃ / min.

2. The method for preparing a silicon nitride substrate according to claim 1, characterized in that, The silicon nitride is α-Si3N4 with a purity >99% and a particle size D. 50 0.4~1.0µm; or / and The rare earth compound is one of Yb2O3, Y2O3, or a mixture thereof.

3. A silicon nitride substrate, characterized in that, Made from the following ingredients: Silicon nitride 88~93 wt% Enstatite microcrystalline glass 4~7 wt% Rare earth compounds 2~5 wt% The enstatite microcrystalline glass is made of the following components: 50-55 wt% raw sodium sand ore 1-5 wt% high-alumina 35-40 wt% calcined talc in the billet 1-5 wt% of calcium feldspar Potassium feldspar 1~5wt% albite 1~5wt%; The enstatite microcrystalline glass is prepared by the following steps: Q1. Dry the raw sodium sand, high alumina clay, calcined talc, calcium feldspar, potassium feldspar, and sodium feldspar mineral raw materials separately to remove moisture. Q2. Weigh out the raw sodium sand, high alumina clay, calcined talc for billet, calcium feldspar, potassium feldspar and sodium feldspar according to the formula, mix them evenly and place them in an alumina crucible. Q3, the alumina crucible is placed in an air sintering furnace for sintering at a heating rate of 1~10℃ / min, a melting temperature of 1500~1600℃, and a holding time of 2~4h. Then the molten liquid is poured into a water tank for water quenching to obtain glass frit, and the glass frit is dry-ground to obtain glass powder. Q4, glass powder is ball-milled for 1-3 hours to form a slurry; Q5. Place the slurry in a spray granulation tower for granulation to obtain spherical powder. The spherical powder is then dry-pressed into block samples. Q6. Obtain enstatite microcrystalline glass by powder sintering of block samples, wherein the heating rate is 1~10℃ / min, the nucleation temperature of enstatite microcrystals is 800~900℃, the holding time is 1~2h, the crystallization temperature is 1100~1200℃, and the holding time is 2~4h. The silicon nitride substrate is prepared by the following steps: S1, ball milling: take silicon nitride and sintering aid, mix and ball mill to form ceramic slurry; S2, molding: After degassing, aging and sieving, the ceramic slurry is cast into a silicon nitride green ceramic tape. S3, Degreasing: Silicon nitride green ceramic belt is used for degreasing to remove organic matter from the green body and obtain degreasing sheet; S4, Sintering: Degreased sheets are sintered to form a silicon nitride sintered substrate; In S2, the aging time is 3~665h, and the thickness of the green ceramic belt is 0.1~0.8mm; in S3, the degreasing atmosphere is nitrogen, the flow rate is 100~300L / min, the degreasing temperature is 500~600℃, the degreasing time is 5~10h, and the heating rate is 1~5℃ / min; in S4, the sintering atmosphere is nitrogen, the pressure is 1~3MPa, the sintering temperature is 1750~1850℃, the holding time is 3~6h, and the heating rate is 1~5℃ / min.

4. The silicon nitride substrate according to claim 3, characterized in that, The silicon nitride substrate has a flexural strength > 800 MPa, thermal conductivity > 80 W / mK, and density > 3.2 g / cm³. 3 Warpage ≤ 0.3%.

Citation Information

Patent Citations

  • High-toughness ceramic material and preparation method thereof

    CN106588030A

  • Microcrystalline glass device

    CN110550865A